2018
DOI: 10.1002/admi.201801279
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Interfacial Adhesion and Thermal Stability in Bismuth Telluride/Nickel/Copper Multilayer Films with Low Electrical Contact Resistance

Abstract: The interfacial property between thermoelectric films and metal electrodes greatly affects the performance and practical application of thin‐film thermoelectric devices. Here, Ni intermediate layer is chosen and inserted into Bi2Te3/Cu to simultaneously regulate the electrical and mechanical performance of the interface. Meanwhile, Ar/H2 plasma cleaning is also adopted to optimize the interfacial connection during the sputtering process. Results show the interfacial element diffusion can be effectively blocked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 37 publications
2
22
0
2
Order By: Relevance
“…Contact resistivity can be affected by many factors including the crystallinity of the metal layer, the surface cleanness and roughness of the substrates, and the deposition methods. It has been reported that high crystallinity and smooth interface yield low contact resistivity. , If the metal layers were deposited by sputtering and in contact with Bi 2 Te 3 , the contact resistivities for the as-deposited samples are from 10 –10 to 10 –8 Ω·m 2 . Applying Ar plasma to clean the Bi 2 Te 3 surface prior to metal deposition and annealing the whole joints at 100 °C for 2 h can further reduce the contact resistivity to 10 –12 Ω·m 2 . By using E-beam evaporating or electroplating methods to deposit the metal contacts, the contact resistivity would be around 10 –11 to 10 –8 Ω·m 2 . …”
Section: Resultsmentioning
confidence: 99%
“…Contact resistivity can be affected by many factors including the crystallinity of the metal layer, the surface cleanness and roughness of the substrates, and the deposition methods. It has been reported that high crystallinity and smooth interface yield low contact resistivity. , If the metal layers were deposited by sputtering and in contact with Bi 2 Te 3 , the contact resistivities for the as-deposited samples are from 10 –10 to 10 –8 Ω·m 2 . Applying Ar plasma to clean the Bi 2 Te 3 surface prior to metal deposition and annealing the whole joints at 100 °C for 2 h can further reduce the contact resistivity to 10 –12 Ω·m 2 . By using E-beam evaporating or electroplating methods to deposit the metal contacts, the contact resistivity would be around 10 –11 to 10 –8 Ω·m 2 . …”
Section: Resultsmentioning
confidence: 99%
“…Deng et al. [ 237 ] developed a strategy to optimize the interfacial connection of the Bi 2 Te 3 film by introducing an Ni layer between the Bi 2 Te 3 film and the Cu film electrode. Ar‐H 2 plasma cleaning was used to optimize the interfacial connection during the sputtering process.…”
Section: Challengesmentioning
confidence: 99%
“…For typical Bi 2 Te 3 -based devices, a thin nickel layer of 0.5-10 mm is usually employed through electrochemical deposition, electroless plating, or magnetic sputtering before the soldering process. Deng et al [237] developed a strategy to optimize the interfacial connection of the Bi 2 Te 3 film by introducing an Ni layer between the Bi 2 Te 3 film and the Cu film electrode. Ar-H 2 plasma cleaning was used to optimize the interfacial connection during the sputtering process.…”
Section: Thermoelectric Materials-electrodes Interface In Thermoelect...mentioning
confidence: 99%
“…Low values of contact resistance in semiconductormetal contact structure significantly complicate its experimental determination. The method of contact resistance measurement similar to well-known method of TLM (Transmission line method) [8,[15][16][17][18] is proposed in this study.…”
Section: Introductionmentioning
confidence: 99%